IGRP and insulin vaccination induce CD8+ T cell‐mediated autoimmune diabetes in the RIP‐CD80GP mouse. (May 2014) - Fuchs, Y. F.; Adler, K.; Lindner, A.; Karasinsky, A.; Wilhelm, C.; Weigelt, M.; Balke, H.; Förtsch, K.; Mortler‐Hildebrandt, L. F.; Harlan, D. M.; Pechhold, K.; Ziegler, A.‐G.; et al.
Summary Autoimmune diabetes is characterized by autoantigen‐specific T cell‐mediated destruction of pancreatic islet beta cells, and CD8+ T cells are key players during this process. We assessed whether the bitransgenic RIP‐CD80 x RIP‐LCMV‐GP (RIP‐CD80GP) mice may be a versatile antigen‐specific model of inducible CD8+ T cell‐mediated autoimmune diabetes. Antigen‐encoding DNA, peptide‐loaded dendritic cells and antigen plus incomplete Freund's adjuvant were used for vaccination. Of 14 pancreatic proteins tested by DNA vaccination, murine pre‐proinsulin 2 (100% of mice; median time after vaccination, 60 days) and islet‐specific glucose‐6‐phosphatase catalytic subunit‐related protein (IGRP) (77%, 58 days) could induce diabetes. Vaccination with DNA encoding for zinc transporter 8, Ia‐2, Ia‐2β, glutamic acid decarboxylase 67 (Gad67), chromogranin A, insulinoma amyloid polypeptide and homeobox protein Nkx‐2.2 induced diabetes development in 25–33% of mice. Vaccination with DNA encoding for Gad65, secretogranin 5, pancreas/duodenum homeobox protein 1 (Pdx1), carboxyl ester lipase, glucagon and control hepatitis B surface antigen (HBsAg) induced diabetes in <20% of mice. Diabetes induction efficiency could be increased by DNA vaccination with a vector encoding a ubiquitin–antigen fusion construct. Diabetic mice had florid T cell islet infiltration. CD8+ T cell targets of IGRP were identified with a peptide library‐based enzyme‐linked immunospot assay, and diabetes could also be induced by vaccination with major histocompatibility complex (MHC) class I‐restricted IGRP peptides loaded on mature dendritic cells. Vaccination with antigen plus incomplete Freund's adjuvant, which can prevent diabetes in other models, led to rapid diabetes development in the RIP‐CD80GP mouse. We conclude that RIP‐CD80GP mice are a versatile model of antigen specific autoimmune diabetes and may complement existing mouse models of autoimmune diabetes for evaluating CD8+ T cell‐targeted prevention strategies.